A Comparison of Educational Models under Cultural Differences between Collectivism and Individualism in China and the West (International Journal of Scientific Research and Management (IJSRM), 2024)
By focusing on the differences between China and the West in terms of collectivist and individualist ideologies and cultures, this paper compares and analyzes the different modes of education produced by China and the West under these two types of cultural backgrounds. It explains the advantages and disadvantages of Chinese and Western education in terms of the way educators teach knowledge and the different educational philosophies. The Chinese and Western educational models need to exchange and learn from each other, and at the same time, based on their own national conditions, to respond to the pace of development in the new era with innovative reforms and reasonable absorption of each other’s experiences.